Cd-doped Ag2O/BiVO4 visible light Z-scheme photocatalyst for efficient ciprofloxacin degradation - De A.K.; Kumar U.; Jatav N.; Sinha I. (My University, 2025)
Foreign element doping can produce new photocatalysts with different band edge positions and adsorption properties. A composite of such a doped semiconductor with another component should enhance its photocatalytic properties towards a target substrate. The present investigation used a simple hydrothermal protocol to prepare Cd-doped Ag2O nanoparticles. The Cd-doping of Ag2O nanoparticles changed its valence band maximum position from 0.8 eV (for undoped Ag2O nanoparticles) to 2.67 eV with a slight narrowing of the Ag2O bandgap. A combination of DFT calculation and XRD results showed that the dopant Cd substituted Ag in the Ag2O lattice. The doped material is an effective photocatalyst for ciprofloxacin degradation but with poor recyclability. The joining of a BiVO4 part to the Cd-doped Ag2O nanostructures gave a composite with improved photocatalytic activity and recyclability towards ciprofloxacin degradation. DFT calculations showed that BiVO4 has a higher oxygen affinity than Cd-doped Ag2O. The XPS characterization of the composite and appropriate active species scavenger experiments demonstrated a Z-scheme mechanism. Superoxide radicals play a critical role in CIP degradation. © 2022 The Royal Society of Chemistry.